Investigation of the first reported outbreak of New Delhi metallo-β-lactamase-1-producing Pseudomonas aeruginosa in Texas - Madhuri M. Sopirala; Kathleen Hartless; Sherry Reid; Angela Christie-Smith; Jeanette Fiveash; Aderonke Badejogbin; Andrew Otto Psenicka (Cambridge University Press, 2023)
We describe an epidemiologic investigation and successful control measures for the first reported outbreak of blaNDM-1-carrying Pseudomonas aeruginosa in Texas occurring in a veteran with transmission of the same organism and a blaNDM-5-carrying Escherichia coli, respectively, to two roommates and blaNDM-carrying organism/s to a patient cared for by common staff.